Hedonic And Physicochemical Quality Test Of Biscuits With Chicken Liver Flour And Pumpkin Flour Substitution As Supplementary Food For Pregnant Women - Masruro Masruro; Noor Rohmah Mayasari (CV. AFDIFAL MAJU BERKAH, 2026)
Pregnancy requires optimal nutrition, but physiological changes increase the risk of Chronic Energy Deficiency (CED). As a solution to the government's supplementary (PMT) biscuit, which is less preferred in terms of aroma and flavor, an innovation of nutrient-dense biscuits was developed by substituting chicken liver flour and pumkin flour. This study aimed to determine the effect of substitution of chicken liver flour and pumpkin flour on the hedonic quality (colour, aroma, taste and texture (crispiness)) and physicochemical (moisture, ash content, and density). This study used an experimental design with 9 formulations of substitute biscuits, containing chicken liver flour levels at 20%, 25%, and 30% and pumkin flour levels at 5%, 10%, 15%. Sensory evaluation was conducted by 36 untrained panelists, and the results were analyzed using Kruskal-Walis and post hoc Mann-Whitney. Laboratory analysis was evaluating moisture content, ash content, and density. Substitution of chicken liver flour and pumpkin flour showed an effect on the color parameter (p<0.05). The characteristics of biscuits were yellowish-brown color (3.90), with the chicken liver aroma (3.89) and pumkin aroma (3.70) being almost imperceptible, the taste of chicken liver (3.27) and taste of pumkin (3.35) was faint, and the texture was slightly crispy (3.05). Physicochemical analyzes showed a moisture content of 4.68-4.77%, ash content of 1.77-2.42%, and density of 9.91-35.47 N. Biscuits substituted with chicken liver flour and pumpkin flour were sensory accepted by panelists and had good physicochemical characteristics. Future research should conduct shelf-life testing, evaluate other chemical contents, control during the production process, and sensory evaluation by semi-trained panelists.